A countrywide programme of continuing professional development in Argentina. Issue 6 (1st June 1998) - Lejarraga, H; Ageitos, M L; Galli, A; Castro, C; Paediatrics, Argentine Society of; Education, Subcommittee of Continuing Paediatric
Abstract : The Argentinean Society of Paediatrics introduced in 1993 a continuing professional development (CPD) programme to raise standards of clinical practice. The aims of the project were to introduce a structured, distance learning programme accessible to all paediatricians in the country, but especially for those working far from centres of paediatric excellence. The programme is planned on an annual basis. It includes four activities: a written manual designed by a team of medical experts and educationalists comprising 12 topics; field work for participants; annual meetings in several locations in the country for discussion of the subjects; and an evaluation based on centrally designed multiple choice questions distributed by mail. In spite of a registration fee of £90 a year, participation in the programme increased from 3357 in 1993 to 4126 in 1996, from a membership of 10 216 paediatricians in Argentina. The popularity of the programme may result from an appropriate interpretation of professional needs of paediatricians in Argentina, adequate organisational arrangements that reach all colleagues, including those working in remote areas, and a genuine motivation of paediatricians for participating in a learning process.